2018
DOI: 10.1186/s12867-018-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of NPAS3 functional domains and variants

Abstract: BackgroundNPAS3 encodes a transcription factor which has been associated with multiple human psychiatric and neurodevelopmental disorders. In mice, deletion of Npas3 was found to cause alterations in neurodevelopment, as well as a marked reduction in neurogenesis in the adult mouse hippocampus. This neurogenic deficit, alongside the reduction in cortical interneuron number, likely contributes to the behavioral and cognitive alterations observed in Npas3 knockout mice. Although loss of Npas3 has been found to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 81 publications
3
10
0
Order By: Relevance
“…Very recently, Luoma et al tested the localization of the canonical human NPAS3 isoform (933aa) in HEK293T cells. The bHLH domain was localized in the cytoplasm, what they discussed as consistent with the result of their predictions with NetNES server [77]. However, no experimental verification of predicted NES was performed.…”
Section: Regulation Of the Subcellular Localization Of Class I Bhlsupporting
confidence: 58%
See 1 more Smart Citation
“…Very recently, Luoma et al tested the localization of the canonical human NPAS3 isoform (933aa) in HEK293T cells. The bHLH domain was localized in the cytoplasm, what they discussed as consistent with the result of their predictions with NetNES server [77]. However, no experimental verification of predicted NES was performed.…”
Section: Regulation Of the Subcellular Localization Of Class I Bhlsupporting
confidence: 58%
“…The expressed C-terminal part of protein (451-951aa) was detected exclusively in the nucleus. Further analysis revealed that NPAS3 alone is present both in nucleus and cytoplasm, while co-expression with ARNT resulted in mainly nuclear localization [77]. Our predictions (Table 1, Supplementary Materials 1, Supplementary Materials Summary) revealed high probability of the presence of NLSs in bHLH domain (29-78aa), PAS-1 domain (130-161aa), linker between PAS domains (266-297aa) and C-terminal part of protein (727-773aa).…”
Section: Regulation Of the Subcellular Localization Of Class I Bhlmentioning
confidence: 99%
“…In fact, V304I was identified as an NPAS3 missense variant associated with psychiatric disorders. Although the V304I mutation located in the PAS linker did not alter the protein’s molecular function, mutation in the disordered region of NPAS3 led to the aggregation of this protein, which resulted in schizophrenia [ 111 , 112 ]. This has led us to hypothesize that some mutations could impact IDRs, thus promoting their misfolding and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…V304I mutation located in PAS linker did not altered protein' molecular function, however was sequestered in the insoluble fraction of cell lysates, suggesting aggregation of protein. The second mutation A552P located in C-terminus, was documented to be sufficient for activation of reporter gene expression [105].…”
Section: Discussionmentioning
confidence: 99%